INDEKS HARGA SAHAM GABUNGAN (IHSG), NILAI TUKAR RUPIAH DAN BI 7- DAY REVERSE REPO RATE (BI RATE) TERHADAP NILAI AKTIVA BERSIH REKSA DANA - Chaerudin, Abdul Rauf; Setiyowati, Setiyowati (LP2M Universitas Bina Bangsa, 2025)
The mutual fund's net asset value is the total value of all securities in the mutual fund based on the closing market price of each security, then deducted by mutual fund obligations, such as investment manager fees, custodian bank fees, transaction costs, auditor fees, tax fees, and other fees. related to investment management. The purpose of this study is to determine the effect of the Composite Stock Price Index (IHSG), Rupiah Exchange Rate and BI 7 – Day Reverse Repo Rate on Net Asset Value of Mutual Funds in 2019-2022, either partially or simultaneously. This study uses a quantitative research method. The population is the entire net asset value of mutual funds from January 2019 to December 2022 with a total of 48 data, as well as the number of samples using the saturated sampling technique in this study as many as 48 data from the net asset value of mutual funds starting from January 2019 to December 2022. The results of this research hypothesis 1 obtained tcount > ttable with a value of 7.850 > 2.015 with a significance level of 0.00 <0.05,Ho was rejected and Ha was accepted, hypothesis 2 obtained -tcount < -ttable with a value of -6.755 < -2.015 with a significance level of.00 <0.05, Ho was rejected and Ha was accepted, hypothesis 3 obtained -tcount < -t table with a value of -8.195 < -2.015 with a significance level of 0.00 <0.05, Ho was rejected and Ha was accepted, hypothesis 4 is obtained Fcount > Ftable 57.641 > 2.8, Ho was rejected and Ha was accepted simultanesously. Based on the results of research hat has been done, it states that the effect of the Composite Stock Price Index (IHSG) has a positive effect on Net Asset Value of Mutual Funds, rupiah exchange rate has negative effect on Net Asset Value of Mutual Funds, BI 7 – Day Reverse Repo Rate has negative effect on Net Asset Value of Mutual Funds and simultanesously the effect of the Composite Stock Price Index (IHSG), rupiah exchange rate, and BI 7 – Day Reverse Repo Rate have a significant effect on Net Asset Value of Mutual Funds